Communication gap between analogue parents and digital children - Boranijašević, Marija R. (Sociološki pregled, 2021)
The conducted research is aimed at determining whether there are any differences, and to what extent, in communication practice between parents and their children today. The subject of the research refers to communication habits of parents and their children, as well as their mutual communication. The task is to determine whether the parents belonging to Generation X and Baby Boom Generation, characterized by the “analogue” approach to communication, and their children belonging to “digital” Generation Z, actually communicate in a different manner and generally belong to two groups: Digital Residents or Digital Visitors.
Keywords: communication; Digital Residents; Digital Visitors; parents; children